Pediatric Traumatic Cervicothoracic Extradural Arachnoid Cyst - Tadele, Abrham; Egziabher, Biniam G.; Egziabher, Milena G.; Mesfin, Fasil; Bergene, Eyerusalem (WFNS Journal, 2025)
Background Extradural spinal arachnoid cysts are an uncommon cause of myelopathy in pediatric populations, typically originating from congenital defects in the dura mater. However, there are no documented cases of multiple traumatic arachnoid cysts in children.Case Description We report on a 3-year-old girl who presented with persistent neurologic deficits following a trauma, later diagnosed with multiple posttraumatic extradural arachnoid cysts. This is the first documented case of its kind in the literature.Conclusion The definitive treatment for these cysts is surgical resection of the cyst wall and obliteration of the defect. This case underscores the importance of considering traumatic origins in the differential diagnosis of pediatric myelopathy.
Keywords: extradural arachnoid cyst; traumatic; multiple arachnoid cyst; pediatric